Design and Function of a Circulation Phantom for the Bolus Tracking Technique Use on a Computer Tomograph - Mach, Georg; Messner, Klemens; Miljković, Uroš; Stojkovska Krkalović, Tatjana; Deutsch, Christopher (Scripta Medica, 2025)
Background/Aim: Bolus tracking (BT) is a widely adopted technique for both the administration and monitoring of contrast media in computed tomography (CT) scans. The aim of this study was to create a circulation phantom for the BT technique for CT. The phantom has been tested for functionality and is intended to be used for teaching radiology technology students.Methods: Contrast media acquisitions were performed in a circulation phantom. Test setup with five different flow rates (2 [mL/s], 3 [mL/s], 4 [mL/s], 5 [mL/s] and 6 [mL/s]) were used for each cannula size with different gauge (G) units (22 G, 20 G, 18 G and 17 G). Each cannula's trigger time (TT) was measured three times with each flow. A total of 60 measurements were performed to show the functionality.Results: The measurements have shown that in each cannula with a flow of 2 [mL/s] and 3 [mL/s], BT was triggered at roughly 100 HU at the same time. If the flow was higher than 3 [mL/s], the blue cannula with 22 G deviates from the others by one second until BT is triggered.Conclusion: The function of the phantom was verified. The CT started the scan automatically using the BT technique. The verification was performed for each cannula size and each flow.
Keywords: Tomography, computed; Bolus tracking; Phantoms, imaging; Contrast media; Flow rate